1984
DOI: 10.12938/bifidus1982.3.1_29
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Bifidobacterium Administration in Patients with Leukemia

Abstract: The intestinal flora of patients with leukemia was changed by chemotherapy. In many cases, Klebsiella, Citrobacter, and Proteus vulgaris, etc., which are normally sparse, increased greatly. Anaerobic bacteria, especially Bacteroides, also increased. Many cases of Candida overgrowth were also observed. This imbalance of intestinal microorganisms was counteracted by oral Bifidobacterium administration. Endotoxin in the blood and indican in the urine were tested in leukemia patients. These tests were positive in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0
1

Year Published

1988
1988
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 10 publications
0
7
0
1
Order By: Relevance
“…These bacteria are becoming recognized worldwide because of their health and nutritional benefits such as potential beneficial roles in the human intestinal tract (KURMANN & RASIC, 1991;ROBINSON & SAMONA, 1992;VIJAYENDRA & GUPTA, 1992;HOOVER, 1993). Antitumorigenic activity, improvement of lactose-tolerance, reduction of serum cholesterol levels, reduction of ammonia and free serum phenol in patients with liver disease, synthesis of vitamins, increased immunocompetence and antagonistic effects towards enteropathogenic bacteria have all been deviled (POUPARD et al, 1973;ANAND et al, 1984;KAGEYAMA et al, 1984;OKAMURA et al, 1986;UEDA, 1986;YAMAZAKI et al, 1985;HUGHES & HOOVER, 1991;HOOVER, 1993;ISHIBASHI & SHIMAMURA, 1993;DAVIDE, 1995;KEBARY, 1995;SUZUKI, 1995;JIANG et al, 1996;ZOMMARA et al, 1996;BADAWI & EL-SONBATY, 1997;KAILASAPATHY & RYBKA, 1997;ATHRAYILKKALATHIIL & PRASAD, 1997). It is estimated that over 70 products containing bifidobacteria are produced worldwide (HUGHES & HOOVER, 1991;SHAH, 1997).…”
mentioning
confidence: 99%
“…These bacteria are becoming recognized worldwide because of their health and nutritional benefits such as potential beneficial roles in the human intestinal tract (KURMANN & RASIC, 1991;ROBINSON & SAMONA, 1992;VIJAYENDRA & GUPTA, 1992;HOOVER, 1993). Antitumorigenic activity, improvement of lactose-tolerance, reduction of serum cholesterol levels, reduction of ammonia and free serum phenol in patients with liver disease, synthesis of vitamins, increased immunocompetence and antagonistic effects towards enteropathogenic bacteria have all been deviled (POUPARD et al, 1973;ANAND et al, 1984;KAGEYAMA et al, 1984;OKAMURA et al, 1986;UEDA, 1986;YAMAZAKI et al, 1985;HUGHES & HOOVER, 1991;HOOVER, 1993;ISHIBASHI & SHIMAMURA, 1993;DAVIDE, 1995;KEBARY, 1995;SUZUKI, 1995;JIANG et al, 1996;ZOMMARA et al, 1996;BADAWI & EL-SONBATY, 1997;KAILASAPATHY & RYBKA, 1997;ATHRAYILKKALATHIIL & PRASAD, 1997). It is estimated that over 70 products containing bifidobacteria are produced worldwide (HUGHES & HOOVER, 1991;SHAH, 1997).…”
mentioning
confidence: 99%
“…Furthermore, this strain has been administered to immunocompromised patients with leukemia treated with anticancer drugs including cyclophosphamide to confirm the effect of probiotics on Candida infection. Kageyama et al (1984) observed that Candida that had proliferated in patients after administration of antileukemic drug was reduced by Bifidobacterium administration and no adverse event was induced by the probiotic. B. longum BB536 was administered to germfree mice and translocation to liver, mesenteric lymph nodes, and kidney was observed by culturing the organs.…”
Section: Translocation Of Probiotics and Virulencementioning
confidence: 96%
“…Kohlenhydrate (Ballaststoffe) nämlich, die weder von den Pankreasenzymen noch von den Dünndarmenzymen gespalten werden -Fructooligosaccharide, Isomaltooligosaccharide, Lactulose -führen offenbar zu einer Vermehrung der Bifidobakterien mit Milieuverschiebungen in Richtung erniedrigter pH-Werte (46). Ernährungsphysiologisch haben Sauermilchprodukte einen hohen Stellenwert (19,23,53). Eine Beeinflussung der Darmflora durch Joghurtzubereitungen ist anhand von zwei Produkten untersucht und beschrieben (4,9,13,26).…”
Section: Beeinflussung Des Mikroökologischen Gleichgewichts Im Darmunclassified